2014
DOI: 10.21273/horttech.24.5.610
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Student Learning From an Experiential Module in a Greenhouse Management Course Using Hydroponics and Recirculating Solution Culture

Abstract: Student learning from producing crops in recirculating culture for a 6-week module in the Fall 2013 course HORT 570 Greenhouse Operations Management at Kansas State University was assessed. The module design followed Kolb’s experiential learning model, with teams of students responsible for production of lettuce (Lactuca sativa ‘Green Oak Leaf’) or basil (Ocimum basilicum ‘Italian Large Leaf’) and chives (Allium schoenoprasum Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Experiential learning generally leads to positive academic outcomes (Bauerle and Park, 2012;Craver and Williams, 2014;Pritts, 2017;St. Hilaire et al, 2009;Uchanski et al, 2015), but not all activities have the same impact on learning (Holstermann et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiential learning generally leads to positive academic outcomes (Bauerle and Park, 2012;Craver and Williams, 2014;Pritts, 2017;St. Hilaire et al, 2009;Uchanski et al, 2015), but not all activities have the same impact on learning (Holstermann et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Hilaire et al, 2009;Uchanski et al, 2015). Additionally, experiential learning enhances lower-and higher-order learning (Craver and Williams, 2014) and promotes skill development (Mahoney et al, 2015) in advanced horticulture courses. Experiential learning also aids in recruiting students into subsequent horticulture courses (Pritts, 2017).…”
mentioning
confidence: 99%
“…One of the reasons for this lag in adoption is that hands-on activities, laboratories, and field trips (collectively called experiential learning) are commonplace in horticulture education but their implementation in online courses is challenging. Experiential learning enhances the student experience (Lindsey, 2019;Nunez, 2020), promotes learning, and fosters skill development (Craver and Williams, 2014;Fry et al, 2021;St. Hilaire et al, 2009;Uchanski et al, 2015).…”
Section: U Niversities Have Been Offeringmentioning
confidence: 99%
“…(Yuvaraj and Subramanian, 2020). Several studies revealed that hydroponics is contributed to enhancing agriculture productivity by avoiding the environmental limitations at a large-scale (Craver and Williams, 2014). Mainly, ecological factors like temperature, humidity, and light intensity can be maintained or manipulated in a hydroponics system to avoid a decrease in crop productivity due to uncomfortable environmental conditions (Ruiz andTaleisnik, 2013 andSmeets et al, 2008).…”
Section: Introductionmentioning
confidence: 99%